Petrography and Sedimentology of the Ghundai Sar Reef Complex, Jamrud; Khyber Agency; Pakistan - Khan, Muhammad Attaullah (Journal of Himalayan Earth Sciences, 1979)
A belt of Siluro-Devonian Coralline limestone of pink, yellowish-pink, and grayish-white colour is exposed in the hills of Ghundai Sar, near Jamrud; Khyber Agency. The entire formation represents deposition on a stable shelf. The environments were conductive for the development of coral reef. The ortho-quartzite associated with dolomite and limestone supports this observation. In this paper, petrography and sedimentology of the reef limestone is discussed in detail. 101 specimens were collected and 30 sections were cut to describe the petrography. The limestone and dolomite show variations in their mineralogical composition. All variations from arenaceous limestone to calcareous ortho-quartzite occur.